2015
DOI: 10.1007/s11856-015-1234-0
|View full text |Cite
|
Sign up to set email alerts
|

Measuring definable sets in o-minimal fields

Abstract: We introduce a non real-valued measure on the definable sets contained in the finite part of a cartesian power of an o-minimal field R. The measure takes values in an ordered semiring, the Dedekind completion of a quotient of R. We show that every measurable subset of R n with non-empty interior has positive measure, and that the measure is preserved by definable C 1 -diffeomorphisms with Jacobian determinant equal to ±1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 11 publications
0
19
1
Order By: Relevance
“…rOmpA has been associated with adherence to and invasion of human endothelial cells by interacting with integrin alpha2beta1 (Hillman et al, 2013). The tandem repeat structure was first analyzed in the rompA gene of R. rickettsii (Anderson et al, 1990), but the functions of the tandem repeats remain to be elucidated. Our analysis showed that the tandem repeat regions in rompA are composed of three very similar sequences of 225, 216, and 216 bp in the two species (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…rOmpA has been associated with adherence to and invasion of human endothelial cells by interacting with integrin alpha2beta1 (Hillman et al, 2013). The tandem repeat structure was first analyzed in the rompA gene of R. rickettsii (Anderson et al, 1990), but the functions of the tandem repeats remain to be elucidated. Our analysis showed that the tandem repeat regions in rompA are composed of three very similar sequences of 225, 216, and 216 bp in the two species (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…However, the argument about the saturated field is quite complicated, so we do not discuss it here. See for details.…”
Section: Semialgebraic Chains and Integrationsmentioning
confidence: 99%
“…Then, by using Theorem 1.1, we can show that v n is uniformly bounded in R, that is, there is c ∈ R such that v (d) n (X) < c for any n ∈ N. Moreover, the dth Hausdorff measure H d (X) (or the volume) of X is given by lim n→∞ v (d) n (X), which exists in some saturated field containing R. However, the argument about the saturated field is quite complicated, so we do not discuss it here. See [11] for details.…”
Section: Integrals Of Differential Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measure theory of real closed fields is delicate for these fields are generally not complete topological spaces (for their natural topology). Recently, T. Kaiser [4] introduced a generalized Lebesgue measure for semi-algebraic sets on real closed fields (see also [8]). It would be interesting to investigate the extent to which the estimate we give on the geometry of the set of generalized critical values is related to the Lebesgue measure introduced in [4].…”
Section: Introductionmentioning
confidence: 99%